Posterior communicating artery aneurysm presenting as isolated oculomotor palsy: The role of rapid identification, intervention, and multidisciplinary care - A case study - Tedjo, Raden Andi Ario; Subandi, Subandi; Tejomukti, Teddy; Hamidi, Baarid Luqman; Tristan, Christopher Daniel; Hamka, Muhammad Farid; Rahman, Awalil Rifqi Kurnia; Putra, Stefanus Erdana; Hafizhan, Muhammad (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Posterior communicating artery (PCOM) aneurysms are the prevalent type of aneurysm with high rupture risks. Isolated oculomotor nerve (CN III) palsy is a key symptom warranting heightened awareness in primary care. Given the need for advanced imaging, early referral is paramount. This study highlights the significance of prompt identification, targeted intervention, and comprehensive management in optimizing patient outcomes. Case: A 58-year-old woman presented with isolated CN III palsy. The patient underwent rapid referral to tertiary care with magnetic resonance angiography (MRA) and digital subtraction angiography (DSA), revealing an aneurysm in the PCOM. Subsequently, coiling was performed to achieve complete occlusion. The procedure resulted in significant neurological recovery, with restoration of CN III function. Post-coiling, the patient receives close nurse monitoring, incorporating fall management and comprehensive education before discharge. CN III palsy is one of the unique-noticeable presentations of PCOM aneurysms, though symptoms may include facial pain, occasional headaches, and migraines. Coiling was chosen due to its less invasiveness and was recommended for posterior circulation aneurysms. Blood pressure control is essential to prevent aneurysm formation, rupture, and recurrence. Regular imaging follow-ups were needed to ensure long-term outcomes. Conclusion: PCOM aneurysm care involves a multidisciplinary approach. Rapid identification, early referral, immediate occlusion, and comprehensive rehabilitative programs were mandatory to improve patient outcomes.